Rebuilding tour operator companies resilience and performance via business continuity management / Quratul’ain Syahirah Awang Ali - Awang Ali, Quratul’ain Syahirah (2024)
In 2020, the World Health Organisation (WHO) declared Covid-19 as a Global Public Health Emergency, triggering a significant transformation in the worldwide tourism landscape. Multiple nations, including Malaysia, Indonesia, Thailand, the Philippines, and Singapore, reacted by enforcing border closures, travel restrictions, and Movement Control Orders (MCO). The Malaysian tourism industry suffered a severe setback due to the Covid-19 outbreak, with travel agency and tour operator companies in Malaysia reporting a substantial decline of -77.7 percent following the MCO's implementation. To ensure their survival during the pandemic, numerous tour operator companies diversified their services into other industries, underscoring the necessity for comprehensive understanding of business continuity principles to bolster resilience and sustain performance in this sector. Hence, this study aimed to examine the relationship between Business Continuity Management (BCM) practices, organisational resilience, performance, and firm size. Employing a multistage sampling approach encompassing purposive and cluster sampling, the study gathered responses from 331 participants as listed by MOTAC and the data applied into Partial Least Square Structural Equation Modelling (PLS-SEM) for hypothesis testing. The findings indicated that the embeddedness of continuity practices and adaptive resilience had a profound and influential impact on organisational resilience and performance as compared to other BCM practices. Additionally, the study found that the size of tour operator companies in Malaysia did not affect organisational resilience or performance significantly, as decision-making processes within these companies were found to be homogenous. Furthermore, the study exposed a lack of comprehensive emergency planning among most tour operator companies for crisis management. Incorporating BCM practices into tour operator companies' survival strategies enables increased resilience, enhance the and continuity of operation. It also helps with regulatory compliance, enhances the supply chain, promotes financial stability, and puts employee well-being first. These criteria together contribute to the company's capacity to effectively manage and recover from disruptions. These findings offer substantial guidance for the relevant authorities, such as the Ministry of Tourism, Arts, and Culture (MOTAC) and Tourism Malaysia, to enhance the National Tourism Policy 2020-2030 and Strategic Plan 2021-2025 by including the emergency strategies within their national plan. This enhancement would encompass tourism resilience in their existing legislation and future directives, thus addressing critical industry challenges.